Revolutionary Kašpárek: The Life Cycle of the Radical Puppet - Stephenson, Cheryl (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2022)
Throughout the Czech National Revival and the final years of the Austro-Hungarian Empire, the puppet stage served as a site of resistance, of advocacy for Czech sovereignty, and criticism of Germanic influences on Czech culture and everyday life. The undisputed star in these efforts was the puppet hero Kašpárek, the little Czech jester who uses his wits to defeat Austro-Hungarian petty bureaucrats, police officers, and other deputies of imperial authority in hundreds of puppet plays throughout the nineteenth and early twentieth centuries. This article explores How Kašpárek Laid Austria to Rest, a 1918 performance which saw Kašpárek’s role shift from one of resistance to one of revolution. In this play, performed in Pilsen (Plzeň) in the final weeks of the First World War, Kašpárek no longer faced off against Austrian officials, but rather met a much larger opponent, the two-headed imperial eagle, symbol of the empire itself. In this performance, Kašpárek does not need to outwit his opponent; he is a dominant force from the start. After beheading the eagle, the performance becomes a kind of funeral mass for the empire with Kašpárek serving as both priest and master of ceremonies, bringing a kind of jubilation to the usually somber context. In this discussion, I examine this turning point from the interconnected perspectives of social history and semiotics. This dual approach exposes both the developments and conditions that allow for this striking symbolic victory on the puppet stage,n but further an exploration of the ways the folk archetype of the jester and, by extension, a folk-based image of Czech national identity navigate radical political change.